2011
DOI: 10.1002/rcm.5189
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for quantification of lipids in nerve tissue using matrix‐assisted laser desorption/ionization mass spectrometric imaging

Abstract: MALDI mass spectrometric imaging is a technique that provides the ability to identify and characterize endogenous and exogenous compounds spatially within tissue with relatively little sample preparation. While it is a proven methodology for qualitative analysis, little has been reported for its utility in quantitative measurements. In the current work, inherent challenges in MALDI quantification are addressed. Signal response is monitored over successive analyses of a single tissue section to minimize error d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…Phospholipid standards applied to a sample holder prior to tissue overlay have been successfully analyzed by MALDI-MSI after migration through the tissue (Landgraf et al, 2011). This demonstrates that a degree of extraction can occur either during matrix application or immediately prior to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipid standards applied to a sample holder prior to tissue overlay have been successfully analyzed by MALDI-MSI after migration through the tissue (Landgraf et al, 2011). This demonstrates that a degree of extraction can occur either during matrix application or immediately prior to it.…”
Section: Discussionmentioning
confidence: 99%
“…This image represents the spatial distribution and relative abundance of that particular lipid-ion, and can be correlated with histological features (Burnum et al, 2009) (Delvolve et al, 2011) (Carter et al, 2011). By adding internal standards, absolute abundances of several lipid classes can be measured with high precision using MALDI-MSI (Landgraf et al, 2011). MALDI-MSI does not require specific antibodies such as those used in immunohistochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when complemented with high‐resolution mass spectrometry, the analyses of biological surfaces can take advantage of the high mass accuracy for direct lipid identification . Recent work has shown that lipid quantification is possible when using internal standards …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the molecular diversity of lipids allows them to perform essential structural, modulating and signaling functions in cells and tissues making them highly desirable imaging targets . Recent MALDI‐MSI studies of lipids led to the development of protocols that afforded higher spatial resolution and addressed the possibility for introduction of quantitative criteria for data analysis …”
Section: Discussionmentioning
confidence: 99%